RASIONALITAS TINDAKAN SOSIAL MASYARAKAT SEKITAR MAKAM TUAN GURU SYEKH ABDURRAHMAN SHIDDIQ (Desa Hidayat Kecamatan Kuala Indragiri Kabupaten Indragiri Hilir) - Surya, Della Febrianti; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted in the Hidayat Village, Kuala Indragiri District, Indragiri Hilir Regency. The purpose of this research is to find out how rational the social actions of the people that occur around the tomb. The actions of rationality include the number of people who make pilgrimages to the tomb, the number of people who open businesses by selling accessories and the high interest of buyers to have these accessories or antidotes. The focus of this research is to find out the activities and benefits that occur around the tomb until now. As for the theory, the author uses Max Weber's Social Action theory in this case and the number of samples in this study amounted to 6 people. The author uses qualitative methods and uses purposive sampling technique. Data instruments are observation, interviews and documentation. From the research conducted, the authors found that this village was also of less concern than the Inhil Ministry of Tourism, seen from the existing infrastructure in the village. While the tradition of pilgrimage that took place in the village of Hidayat according to the native villagers was only limited to the traditions of the surrounding community because Tuan Syekh Abdurrahman Shidiq's teacher during his lifetime was very meritorious, plus he was buried right in Hidayat Village. While rumors about sacred tombs are usually highly trusted by pilgrims from outside the area. But thanks to the tomb the people who live around the tomb have a very positive impact on social, religious and economic aspects. Keywords: Religious Tourism, Tradition, Rationality of Action